Economic Impacts of the 2011 Tohoku-Oki Earthquake and Tsunami. Issue 1 (March 2013) - Kajitani, Yoshio; Chang, Stephanie E.; Tatano, Hirokazu
This paper provides an overview of economic impacts in the first year after the 2011 Tohoku-oki earthquake, tsunami, and nuclear accident—at an estimated ¥16.9 trillion (US$211 billion) in direct damage, the costliest natural disaster on record. Documented costs to date include ¥2.9 trillion in insurance payouts and ¥17.7 trillion in response and recovery budgets by the national government that will be financed largely by tax increases and bonds. In the regions with physical damage, fisheries and agriculture, among other sectors, were very hard hit. The disaster also caused measurable economic impacts well beyond the damage regions, including losses in gross domestic product (GDP), in manufacturing from supply-chain disruptions, and in retail trade and tourism due to restrained consumption and radiation fears. Reduced capacity for generating electricity has led to substantial energy conservation nationwide. Results from applying a loss estimation model demonstrated good agreement with observed post-disaster economic activity.